(untitled) (Al-Qamar, 2024)
Intizar Hussain is one of the innovators in the style and technique of the Urdu novel. Among the changes that Intizar Hussain made in the style of novels, the most important are the mythological events and Devomalai stories. He has also used different incidents of Islamic history as hints, while story making new experiments at the level of syle. Apart from this, he has made extensive use of other elements of style, such as smile, metaphor, irony, symbolism, due to which his style has become unique. Intizar Hussain’s style has based on originality and reality. With regards to the style, they have used everything from the Old Testament, the Gospel, the stories of the prophets, Dev Mala, Buddist, and the attachments of Sophia and have succeeded in creating a style that deserves to be called Urdu novel’s new style. In the novel Basti on the one hand, the simplicity of this style attracts the reader, on the other hand, due to the use of different symbols and Devomalai stories. His style has become very layered and patchy.